Content and Face Validity of the Mackey Childbirth Satisfaction Rating Scale Questionnaire Crossculturally Adapted to Brazilian Portuguese - Fernanda Lopes; Nelson Carvas Júnior; Mary Uchiyama Nakamura; Roseli Mieko Yamamoto Nomura (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective The aim of this study was to determine the content and face validity of the Mackey Childbirth Satisfaction Rating Scale (MCSRS) questionnaire cross-culturally adapted to Brazilian Portuguese. Methods The MCSRS is a questionnaire with 34 items related to childbirth satisfaction. The forward- and back-translated versions were compared with the original material, and 10 experts analyzed each item according to the following criteria: clarity, semantic equivalence, appropriateness, and cultural relevance. The final version was presented to 10 mothers for face validation to ensure the questionnaire would suit the target population. Results The total of 34 items assessed by experts for clarity, semantic equivalence, appropriateness, and relevance showed positive agreement of 0.85, 0.92, 0.97 and 0.97; negative agreement of 0.13, 0.09, 0.04 and 0.04; and total agreement of 0.75; 0.85, 0.94 and 0.94, respectively. Multilevel linear modeling was applied with crossed random effects and with nested random effects for each judge. The intercept of each criterion was as follows: clarity, 0.87; semantic equivalence, 0.92; appropriateness, 0.96; and cultural relevance, 0.96. The overall mean of agreement was 92.8%. The face validity measurement yielded 80% of agreement on the items, all of them clearly understood. Conclusion The final version of the Brazilian Portuguese MCSRS questionnaire had face and content validity confirmed. This instrument of evaluation of maternal satisfaction during childbirth was validated to be applied in the Brazilian female population.